Osteoarthritis of the Manubriosternal Joint: An Uncommon Cause of Chest Pain - Vaishya, Raju (Cureus, 2015)
Osteoarthritis of the manubriosternal joint is a rare cause of chest pain. The diagnosis is difficult, and other serious causes of chest pain have to be ruled out first. We report one case that was treated with fusion of the manubriosternal joint using an iliac crest bone graft with a cervical locking plate and screws with excellent results. Preoperative CT scan images were used to measure the screw length and the drill stop depth. In this case report, we have shown that arthrodesis can be an effective way of treating osteoarthritis of the manubriosternal joint when other measures fail. Furthermore, the use of a cervical locking plate with appropriate and careful preoperative planning affords a safe surgical technique, rapid pain relief, and ultimately, sound and asymptomatic union of the joint.